If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8750 = x(x + 3) Reorder the terms: 8750 = x(3 + x) 8750 = (3 * x + x * x) 8750 = (3x + x2) Solving 8750 = 3x + x2 Solving for variable 'x'. Reorder the terms: 8750 + -3x + -1x2 = 3x + -3x + x2 + -1x2 Combine like terms: 3x + -3x = 0 8750 + -3x + -1x2 = 0 + x2 + -1x2 8750 + -3x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 8750 + -3x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -8750 + 3x + x2 = 0 Move the constant term to the right: Add '8750' to each side of the equation. -8750 + 3x + 8750 + x2 = 0 + 8750 Reorder the terms: -8750 + 8750 + 3x + x2 = 0 + 8750 Combine like terms: -8750 + 8750 = 0 0 + 3x + x2 = 0 + 8750 3x + x2 = 0 + 8750 Combine like terms: 0 + 8750 = 8750 3x + x2 = 8750 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 8750 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 8750 + 2.25 Combine like terms: 8750 + 2.25 = 8752.25 2.25 + 3x + x2 = 8752.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 8752.25 Calculate the square root of the right side: 93.553460652 Break this problem into two subproblems by setting (x + 1.5) equal to 93.553460652 and -93.553460652.Subproblem 1
x + 1.5 = 93.553460652 Simplifying x + 1.5 = 93.553460652 Reorder the terms: 1.5 + x = 93.553460652 Solving 1.5 + x = 93.553460652 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 93.553460652 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 93.553460652 + -1.5 x = 93.553460652 + -1.5 Combine like terms: 93.553460652 + -1.5 = 92.053460652 x = 92.053460652 Simplifying x = 92.053460652Subproblem 2
x + 1.5 = -93.553460652 Simplifying x + 1.5 = -93.553460652 Reorder the terms: 1.5 + x = -93.553460652 Solving 1.5 + x = -93.553460652 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -93.553460652 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -93.553460652 + -1.5 x = -93.553460652 + -1.5 Combine like terms: -93.553460652 + -1.5 = -95.053460652 x = -95.053460652 Simplifying x = -95.053460652Solution
The solution to the problem is based on the solutions from the subproblems. x = {92.053460652, -95.053460652}
| 2n+3.75=7n | | 2s-13=27 | | 3(2p+5)-4(p+3)= | | 1750=x*(x+3) | | 2.3x+5.6=3.4 | | 6a+9=23 | | 7x-10+2x=5-x | | 3/5•20m= | | x+(x*0.32)=255 | | 5-3(1-9x)=3-2(2x+4) | | 4x-4t=2 | | 16fg-2g= | | s-3t=rt | | A/3-=2 | | t=(t+20)+(t+10) | | -5(1-5x)+5(-8x-2)=-5x-45 | | t=(t+10)+(t+20) | | 65(3h)+130=h | | 5-2(7x+2)= | | 8+5x=9x-8 | | 8+5x=8x-8 | | 6p+10=360 | | 24x-22=-4(1-6k) | | A=9/8(h-75) | | (3+7i)+(4+5i)=0 | | 6x+10=360 | | 0.142857= | | x^2-6x+16=7 | | 7j-10=60 | | (2x-8)^2/3 | | 3(y-5)/4-4y=3(y-3)/2 | | -x+14=-5x+6 |